Historical Knowledge, National Identity, and Religious Commitment: Explaining the Predictive Relationship among Students in Indonesia - Aninda, Farida Dwitya; Sudrajat, Ajat; Wijayanti, Finna; Maulana, Wildhan Ichza (Diakronika, 2025)
This research is about analyzing the relationship between mastery of national awakening historical material and nationalism and student religiosity. The study population was 220 students and sampling was carried out using proportional cluster random sampling calculated based on Slovin's formula, resulting in a sample of 148 students. This research uses a quantitative approach. Data collection using test instruments and questionnaires. Question validity is done by product moment correlation using Pearson correlation. The reliability test was performed using Cronbach's Alpha. The data analysis technique was performed by descriptive analysis and prerequisite analysis which included normality test, linearity test, multicollinearity test and heteroscedasticity test, from which multiple linear regression analysis was performed. The results of this research show (1) there is a significant positive relationship between mastery of national awakening historical material and student religiosity; (2) there is a significant positive relationship between nationalism and student religiosity; (3) there is a significant positive relationship between mastery of national awakening historical material and nationalism and student religiosity. The implication of this study is to determine the effect of teaching material on national awakening on strengthening students understanding and religious behaviour.